Canadian landmark cases in forensic mental health - Glancy, Graham (University of Toronto Press, 2020)
Landmark Cases -- Expert Testimony -- Insanity Defence -- Criminal Responsibility -- Clarifying Wrongfulness -- Voluntariness -- Fitness to Stand Trial -- Access to Treatment -- Duty to Warn -- Consent to Treatment -- Assessing Damages.